Will Wallace's Line Save Australia from Avian Influenza? - Hamish I. McCallum; David A. Roshier; John P. Tracey; Leo Joseph; Robert Heinsohn (Ecology and Society, 2008)
Australia is separated from the Asian faunal realm by Wallace's Line, across which there is relatively little avian migration. Although this does diminish the risk of high pathogenicity avian influenza of Asian origin arriving with migratory birds, the barrier is not complete. Migratory shorebirds, as well as a few landbirds, move through the region on annual migrations to and from Southeast Asia and destinations further north, although the frequency of infection of avian influenza in these groups is low. Nonetheless, high pathogenicity H5N1 has recently been recorded on the island of New Guinea in West Papua in domestic poultry. This event increases interest in the movements of birds between Wallacea in eastern Indonesia, New Guinea, and Australia, particularly by waterbirds. There are frequent but irregular movements of ducks, geese, and other waterbirds across Torres Strait between New Guinea and Australia, including movements to regions in which H5N1 has occurred in the recent past. Although the likelihood of avian influenza entering Australia via an avian vector is presumed to be low, the nature and extent of bird movements in this region is poorly known. There have been five recorded outbreaks of high pathogenicity avian influenza in Australian poultry flocks, all of the H7 subtype. To date, Australia is the only inhabited continent not to have recorded high pathogenicity avian influenza since 1997, and H5N1 has never been recorded. The ability to map risk from high pathogenicity avian influenza to Australia is hampered by the lack of quantitative data on the extent of bird movements between Australia and its northern neighbors. Recently developed techniques offer the promise to fill this knowledge gap.